Automotive engine innovation in Francoist Spain through the Sociedad de Técnicos de Automoción (STA), 1949-1974 - Ricard Rosich Argelich (Історія науки і техніки, 2025)
In Spain, there exists a lack of historical-sociological approaches to the professional association of engineers of all kinds in general, and automotive engineers in concrete, due to the absence of any academic trend or school interested in studying the professions. For this reason, the purpose of this article is to examine the technological changes and development of automobile engines manufactured in Spain during the Francoist regime, based on the innovations of professionals working in the Spanish automotive industry explained by themselves. We part from a theoretical framework stated by Cultural History reflections on collective imaginations, which understands them as a mental or conscious frame that can be studied by researchers, to the extent that they are shared between all people taking part in any kind of human group as an identity issue: in our case, the Spanish automotive engineers. In addition, the methodology chosen is the study of historical scientific press, where the review of 32 articles written by engineers for the journal Revista de la STA and published by the Sociedad de Técnicos de Automoción (STA) between 1949 and 1974, provides a glimpse of these people’s collective imagination as they describe their inventions and the entire procedure to achieve them, bringing to light successful discoveries, problems, ill-fated attempts and concerns of all kinds. During the years of Francoist autarky, automotive engineers grappled with the great challenge of overcoming financial adversity and scarce resources to physically produce their innovations in engines, whereas during the developmentalist period, which enjoyed better socio-economic conditions following the Economic Stabilisation Plan of 1959, they undertook new experiments to produce increasingly sophisticated innovations. In its own way, automotive engineers’ work was therefore essential in promoting economic growth in Francoist Spain, leaving behind the poverty of the 1940s and 1950s for the consumer society of the 1960s and 1970s. Ultimately, the article concludes how the Revista de la STA, used as an historical primary source throughout the research, demonstrated its complete preference for innovations promoted by engineers related to automotive state-owned companies, leaving aside those ones from private companies.